Beliefs of vulnerability to HIV/AIDS in young adults in a university context (Research, Society and Development, 2021)
Vulnerability is understood as the possibility of people becoming ill due to different conditions that are influenced by the context in which they are inserted. In this sense, it aims to analyze the beliefs and preventive practices of young adults in a university context about AIDS as factors that can predispose to vulnerability. It was a field, cross-sectional and descriptive study, adopting a quanti-qualitative approach, carried out through a survey. The research was carried out on the campuses of public universities and university centers and private colleges in the state of Paraíba. The sample was intentional and non-probabilistic, consisting of 500 university students, aged between 20 and 29 years, distributed over different academic periods. Seeking to know whether in everyday practices, in relational dynamics, and with more access to information, there is greater prevention, seeking a change in the scenarios of social interactions. The instrument used was a structured and self-administered questionnaire. For the computerized textual analysis, the texts were standardized within the Iramuteq freeware criteria. Through the analysis of the Descending Hierarchical Classification, five thematic categories were found: Invulnerability, Impulsiveness, Lack of Information, Sexual Immaturity and No Condom, which explain the beliefs related to practices that present sexual vulnerabilities and risks of contamination with HIV/AIDS. Thus, it is defended the adoption of policies that aim at preventive behavior based on a social construction, beyond the individual will, but that social and programmatic elements can be interconnected, to guarantee information, condoms and sex-based practice safe.